2021
DOI: 10.1101/2021.04.05.21254944
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the genetic overlap of suicide-related behaviors and substance use disorders

Abstract: Background: Suicide-related behaviors are heterogeneous and transdiagnostic, and may demonstrate varying levels of genetic overlap with different substance use disorders (SUDs). Methods: We used linkage disequilibrium score regression and genomic structural equation models to examine the genetic relationships between several SUDs and suicide-related behaviors. Our analyses incorporated summary statistics from the largest genome-wide association studies (GWAS) of problematic alcohol use (PAU), the Fagerstrom T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 60 publications
(72 reference statements)
3
12
0
Order By: Relevance
“…In an independent ongoing effort that employs twin-sibling biometric models, our preliminary findings suggest moderate to substantial genetic and environmental correlations (genetic correlation [rA] ≈ 0.6–0.7; shared environmental correlation [rC] ≈ 0.7–0.9; nonshared environmental correlation [rE] ≈ 0.5–0.6; Edwards et al, 2021). These results parallel findings from a recent molecular genetic study, which reported a genetic correlation of .52 between suicide attempt and problematic alcohol use (Colbert et al, 2021); this molecular approach precludes estimating environmental correlations.…”
Section: Discussionsupporting
confidence: 84%
“…In an independent ongoing effort that employs twin-sibling biometric models, our preliminary findings suggest moderate to substantial genetic and environmental correlations (genetic correlation [rA] ≈ 0.6–0.7; shared environmental correlation [rC] ≈ 0.7–0.9; nonshared environmental correlation [rE] ≈ 0.5–0.6; Edwards et al, 2021). These results parallel findings from a recent molecular genetic study, which reported a genetic correlation of .52 between suicide attempt and problematic alcohol use (Colbert et al, 2021); this molecular approach precludes estimating environmental correlations.…”
Section: Discussionsupporting
confidence: 84%
“…Six studies performed Mendelian randomizations focused on candidate genes involved with substance use disorders, insomnia, atopic dermatitis, inflammation, and blood lipids. There was no evidence that genes involved in substance use disorders contribute to self‐harm, SA, or SD (Colbert et al, 2021). There was also no evidence that genes involved in atopic dermatitis contribute to SI or SA (Qi & Li, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a recent GWAS conducted in European ancestry samples identified numerous genetic loci implicated in four risky behaviors, including number of sexual partners, drinks per week, lifetime history of smoking, and automobile speeding propensity (Karlson Línner et al, 2019). In terms of the genetic association between risky behaviors and suicide attempt, research has observed moderate positive genetic correlations between risk tolerance (i.e., one's preference for taking risks) and suicide attempts (r g = 0.33) (Colbert et al, 2021). Similarly, using a twin design, other research has indicated that close to 40% of the genetic variation in suicidal behaviors was shared with impulsive-aggressive behaviors (Orri et al, 2020).…”
Section: Risky Behavior Genetics and Suicide Attemptmentioning
confidence: 99%